2015
DOI: 10.1038/srep16313
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical view on material formation during pulsed-laser synthesis of nanoparticles in liquid

Abstract: Pulsed-laser assisted nanoparticle synthesis in liquids (PLAL) is a versatile tool for nanoparticle synthesis. However, fundamental aspects of structure formation during PLAL are presently poorly understood. We analyse the spatio-temporal kinetics during PLAL by means of fast X-ray radiography (XR) and scanning small-angle X-ray scattering (SAXS), which permits us to probe the process on length scales from nanometers to millimeters with microsecond temporal resolution. We find that the global structural evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 57 publications
11
147
1
Order By: Relevance
“…[35] However, other aspects of the nanoparticles formation are still not deeply explored, in particular the interaction of the plasma produced by the ablation (evaluated to be at higher than 2-3000 K) [36] with the solvent, which may decompose, leaving carbon materials on the nanoparticles surface as already proved, for example, for gold nanoparticles synthesized in toluene. In order to explain such results one should recall the fabrication methodology of the presented nanocrystals.…”
Section: Doi: 101002/aenm201601703mentioning
confidence: 99%
“…[35] However, other aspects of the nanoparticles formation are still not deeply explored, in particular the interaction of the plasma produced by the ablation (evaluated to be at higher than 2-3000 K) [36] with the solvent, which may decompose, leaving carbon materials on the nanoparticles surface as already proved, for example, for gold nanoparticles synthesized in toluene. In order to explain such results one should recall the fabrication methodology of the presented nanocrystals.…”
Section: Doi: 101002/aenm201601703mentioning
confidence: 99%
“…This may be a unique feature of the cavitation bubble induced by liquid-phase laser ablation, since the deformation of the cavitation bubble is not observed when it is produced by an ultrasonic power [26,27]. Since it has been found that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], the present experimental results may explain the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation. …”
Section: Discussionmentioning
confidence: 60%
“…The experimental results are consistent with a model calculation which assumes free charges on the gas-liquid boundary. Since it has been shown that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], it is suggested that the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation is the electrical charges stored in the cavitation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…[31,48] The chamber had three windows and four channels, two for target transport and two for water exchange. [31,48] The chamber had three windows and four channels, two for target transport and two for water exchange.…”
Section: Methodsmentioning
confidence: 99%